Penguatan Ketahanan Pangan untuk Pekerja Informal, Dhuafa dan Pedagang Kecil dalam Menghadapi Economic Shock Akibat Pandemi Covid-19 - Hafid Kholidi Hadi; Hujjatullah Fazlurrahman; Nurul Indawati; Khoirur Rozaq; Zainur Rahman; Fandi Fatoni (Abimanyu : Jornal of Community Engagement, 2020)
East Java, especially Surabaya City is the city with the highest number of people affected by the Covid-19 virus. As the capital city of East Java Province, Surabaya is the center of administrative services, offices, services, shopping, industry and other supporting sectors. With the Covid-19 virus pandemic spreading so fast, the provincial governments of East Java and the City of Surabaya issued regulations for working at home, studying at home, and limiting activities that led to large gatherings of people. Problems arise when the activities of schools, agencies, offices are reduced, so small traders, informal workers, motorcycle taxis, and some informal workers are economically affected. As well as government regulations that must be obeyed in tackling the Covid-19 pandemic, it also needs to be understood. This community service has a target of increasing endurance, especially in terms of meeting basic needs. The implementer understands that in terms of their income is directly affected, the provision of these staples is so that they do not experience an economic shock. So that later they can stay active and look for income to meet family needs.